2022
DOI: 10.1136/bmjopen-2021-051962
|View full text |Cite
|
Sign up to set email alerts
|

Is self-management a burden? What are the experiences of women self-managing chronic conditions during pregnancy? A systematic review

Abstract: ObjectiveThis systematic review examines the qualitative literature on women’s experiences of self-managing chronic conditions in pregnancy.DesignSystematic review of qualitative literature. Searches were performed in PubMed and CINAHL from inception to February 2021. Critical interpretive synthesis informed the coding framework and the analysis of the data. The Burden of Treatment theory emerged during the initial analysis as having the most synergy with the included literature, themes were refined to conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Self-management support should be promoted in person-centred care. A review regarding pregnant women who have a chronic condition highlighted that women found the treatment shift towards self-management overwhelming; however, women's anxiety mostly stemmed from insufficient knowledge and understanding of their diagnosed condition [77]. If they have supportive friends and family, alongside supportive clinicians, they are more motivated to undertake self-management [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-management support should be promoted in person-centred care. A review regarding pregnant women who have a chronic condition highlighted that women found the treatment shift towards self-management overwhelming; however, women's anxiety mostly stemmed from insufficient knowledge and understanding of their diagnosed condition [77]. If they have supportive friends and family, alongside supportive clinicians, they are more motivated to undertake self-management [77].…”
Section: Discussionmentioning
confidence: 99%
“…A review regarding pregnant women who have a chronic condition highlighted that women found the treatment shift towards self-management overwhelming; however, women's anxiety mostly stemmed from insufficient knowledge and understanding of their diagnosed condition [77]. If they have supportive friends and family, alongside supportive clinicians, they are more motivated to undertake self-management [77]. Peer support is known to be helpful to women with vulnerabilities during pregnancy [78][79][80] and in those who have experienced pregnancy loss [81], however specialist antenatal classes for women who are experiencing similar pregnancies are rarely provided [82].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that pregnant women may have different motivating factors for selfmanagement than the general population. The primary motivator for pregnant women with different types of diabetes selfmanaging their condition is the health of their baby 104 . This is unlikely to be a motivator for the pregnant women in this systematic review who had musculoskeletal conditions which pose little or no risk to the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…This is unlikely to be a motivator for the pregnant women in this systematic review who had musculoskeletal conditions which pose little or no risk to the foetus. However, barriers to self-management of diabetes during pregnancy including anxiety, lack of understanding, and a lack of support from family and health professionals 104 are likely to be relevant to pregnant women with musculoskeletal conditions. Self-management programmes are known to be effective in managing musculoskeletal conditions amongst non-pregnant populations.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of self-management behavior has not been sufficiently applied since its announcement in 2017 [ 11 ]. Cross-validation was performed for construct validity because, compared with non-pregnant women, pregnant women have different motivating factors for self-management [ 19 ].…”
Section: Methodsmentioning
confidence: 99%